Substitution in the linguistics of text and grammatical thought - Nusoum Awfi Hassoun; Asaad Khalaf Al-Awadi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The textual theory relied on the availability of the seven textual criteria set by de Beaugrand for the textuality of texts in the communicative event. (Substitution) - which we are going to study - is one of the mechanisms of the consistency criterion according to Halliday and Paper Hassan, and it represented the second type of grammatical consistency mechanisms, which represents a form of textual coherence. Substitution has the power of being able to achieve textual coherence in the context of the text used in it, as it depends on the mechanism of contrast between the substituted and the substituted from it based on a tribal relationship between them, which contributes to achieving coherence between the parts of the text with each other, and text scholars haveconfirmedthis verified interconnection. As for the grammatical heritage, the phenomenon of substitution formed two directions for them, one that adopts the substitution approach used to clarify the correct from the corrupt in linguistic uses of the grammarians, as they depend on a compensatory substitution mechanism between the grammatical structures used in certain contexts with the aim of correcting the grammatical rule, or to indicate the correctness of a structure In linguistic uses, and the other side is the idea of textual substitution, which was not explicitly found in the context of their writings, but induction proved the existence of many references received by grammarians that approach the idea of substitution in its textual concept. in the grammaticaheritage.